A suspected case of Progressive Familial Intra-hepatic Cholestasis in a Six-Year-Old Nigerian Child - Anthony Atimati; Paul Ikhurionan (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2019)
Progressive Familial Intra-hepatic Cholestasis (PFIC) is a group of heterogeneous, autosomal recessive disorders characterized by cholestasis, jaundice and mutilating pruritus, mostly in infancy. The incidence of PFIC ranges from 1:50,000 to 1:100,000. There are three subtypes; Types 1 and 2 typically present in the neonatal period and early infancy while Type 3 can present in early infancy, childhood or adolescence. This report is about a 6-year old Nigerian girl who presented with jaundice and severe pruritus of one-month duration and abdominal pain of a week duration. The symptoms were preceded by ingestion of Atropine meant for ocular examination two days earlier. She was well-nourished, deeply icteric, had generalized healing scratch marks and hepatomegaly. The laboratory findings included conjugated hyperbilirubinaemia, moderately elevated liver transaminases and Gamma-Glutamyltransferase enzymes. She was managed for PFIC3 using oral ursodeoxycholic acid with complete resolution of the disease.